Socialisation and Screening of Diabetes Mellitus Awareness Movement in Suka Damai Village: Sosialisasi dan Screening Gerakan Peduli Diabetes Melitus (GeLiDiTus) Bangun Kesadaran Masyarakat Desa Suka Damai Akan Diabetes - Tasya Dian Aulia; Ramadani Jati Pamungkas; Rini Juliani; Dahlan Tampubolon (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Diabetes Mellitus (DM) is a medical condition where blood sugar levels exceed normal limits and are caused by the body being unable to produce the insulin hormone optimally. This disease is a chronic congenital disease that cannot be cured. The knowledge of the people of Suka Damai Village about diabetes mellitus is very minimal. After checking, there were several residents who already had symptoms of diabetes but were only just realizing the early signs. In this socialization there was an explanation regarding the types and meaning of diabetes, symptoms, and prevention of this disease. The subjects of this socialization were elderly residents in Suka Damai Village, Ujung Batu District, Rokan Hulu. The results of this community service show differences in the low level of knowledge and awareness of the community regarding diabetes mellitus from before to after the socialization. Socialization and screening can increase public knowledge about diabetes mellitus